2015
DOI: 10.1016/j.intimp.2015.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine differentially modulates LPS-induced TNFα and IL-6 production in mouse macrophages

Abstract: Paroxetine is a selective serotonin reuptake inhibitor (SSRI) that is clinically used for the treatment of depression in human patients. Because of recent reports on the role of serotonin in modulating inflammation and the link between inflammation and depression, we sought to test the effect of paroxetine directly on macrophage response to an inflammatory stimulus. Lipopolysaccharide (LPS) treatment of mouse macrophages significantly enhanced TNFα and IL-6 production. Paroxetine treatment of macrophages howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 37 publications
4
29
2
3
Order By: Relevance
“…We found no evidence that either of the monoaminergic antidepressant drugs tested (TCA or SSRI) exerted any effect on the response in MDMs to LPS or IFNα. This is in contrast to reports that TCAs reduce proinflammatory signaling in phagocytes,68 and SSRIs have been reported to alter macrophage differentiation and inflammatory signaling 67, 69. SSRIs have also been reported to modulate glucocorticoid actions on monocytes 70.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We found no evidence that either of the monoaminergic antidepressant drugs tested (TCA or SSRI) exerted any effect on the response in MDMs to LPS or IFNα. This is in contrast to reports that TCAs reduce proinflammatory signaling in phagocytes,68 and SSRIs have been reported to alter macrophage differentiation and inflammatory signaling 67, 69. SSRIs have also been reported to modulate glucocorticoid actions on monocytes 70.…”
Section: Discussioncontrasting
confidence: 86%
“…This is in contrast to reports that TCAs reduce proinflammatory signaling in phagocytes, 68 and SSRIs have been reported to alter macrophage differentiation and inflammatory signaling. 67,69 SSRIs have also been reported to modulate glucocorticoid actions on monocytes. 70 Although we found no direct effect of SSRIs or TCAs on macrophage responses to either LPS or IFN , we did observe significant cytotoxicity at concentrations that were <20-fold lower than circulating blood concentrations in treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the anti-inflammatory effects of SSRIs. For example, Durairaj et al 98 showed that the SSRI paroxetine has critical but differential effects on IL-6 and TNF-α production in macrophages, which likely involves distinct mechanisms. Furthermore, Fonseka et al 99 reported that an SSRI can modulate the elevated IL-6-levels associated with major depressive disorder.…”
Section: Pharmacokinetic Analysis Of the Optimized Dh-tenvmentioning
confidence: 99%
“…[ 11 ] More importantly, media containing fetal bovine serum (FBS) has indicated to have high concentrations of serotonin. [ 12 ] Serotonin (5‐HT) can modulate the production of a number of inflammatory cytokines, including IL‐2, IL‐16, IFN‐γ, IL‐1β, TNF‐α, and IL‐6. [ 11 ] Moreover, studies suggested that proinflammatory cytokines increase serotonin reuptake via SERT activity enhancement so neglecting serotonin and SSRIs' mutual interrelations seems inconceivable.…”
Section: Introductionmentioning
confidence: 99%